Tilangānah : ʻavvāmī siyāsat kā daur : tahniyatī kitāb, naẕr-i Ravī Nārāʼin Reḍḍī - Aḵẖtar Ḥasan, 1920-; Narsing Rao, B. (Ravī Narāʼin Reḍḍī Tahniyatī Kameṭī : Milne ke pate, Ḥusāmī Buk Ḍipo, 1983)
Collection of articles on Rāvi Narayaṇareḍḍi, political and social activist from Telangana region, India.